Academic achievement and healthy lifestyle habits in primary school children: an interventional study - Gallotta, Maria Chiara; Bonavolontà, Valerio; Zimatore, Giovanna; Curzi, Davide; Falcioni, Lavinia; Migliaccio, Silvia; Guidetti, Laura; Baldari, Carlo (Frontiers in Psychology, 2024)
Purposes: First, to examine the relationship between primary school children's academic achievement and healthy lifestyle habits. Second, to evaluate the effectiveness of two different 5-month physical education interventions (traditional physical education vs coordinative physical education) on children's academic achievement. Third, to examine whether variations of anthropometric variables, fitness level, gross motor coordination, physical activity level, sedentary time, attentional performance, fruit and vegetable consumption, meal frequency and type of physical education intervention could predict children's academic achievement variations.Methods: Before and after the intervention, Italian language and mathematics skills, anthropometric variables (weight, height, body fat percentage, BMI), physical fitness (aerobic fitness, muscular strength, flexibility), gross motor coordination, attentional performance (processing speed, concentration performance, performance accuracy, attentional and inhibitory control), physical activity level, sedentary time and eating habits (meal frequency, fruit and vegetable consumption) were assessed in 161 Italian primary school children, randomly assigned to a traditional physical education group or to a coordinative physical education group.Results: Physical activity level, gross motor coordination and aerobic fitness moderately predicted mathematics skill (R 2 = 17%). Moreover, physical activity level, aerobic fitness and muscular strength moderately predicted Italian language skill (R 2 = 21%). Intervention type differently affected academic achievement. Specifically, Italian language and mathematics skills significantly improved only after traditional intervention. Fruit consumption increase was positively associated with the improvement in academic achievement. Coordinative physical education intervention was associated with a lower probability of improvement in Italian language and mathematical skills.Motor ability and lifestyle habits may have a positive influence on academic achievement in children. Unexpectedly, traditional physical education intervention resulted to be more effective on both Italian language and mathematical skills.